Flood Risk Management in Development Projects: A Review of Malaysian Perspective within the Sendai Framework for Disaster Risk Reduction 2015-2030 - Mohammad Syamsyul Hairi, Saad; Mohamad Idris, Ali; Putri Zulaiha, Razi; Noram Irwan, Ramli (Penerbit UMP, 2024)
This study rigorously assesses Malaysia's development projects' alignment with the Sendai Framework for Disaster Risk Reduction 2015-2030 to identify synergies that can be improved, with a focus on flood risk management challenges and opportunities. The primary goal is to establish a flexible framework that integrates national and grassroots initiatives to advance economic, social, and environmental responsibility in conjunction with development objectives. As Malaysia undergoes rapid development, it is increasingly exposed to flood risks, exacerbated by climate change and urbanization. The Sendai Framework provides guidelines to mitigate these escalating threats. Nonetheless, there is a discernible gap in the existing literature that neither adequately evaluates the development patterns amplifying flood risks nor scrutinizes Malaysia's conformity with the Sendai Framework's objectives. Utilizing a systematic and scoping literature review in conjunction with a qualitative approach. The findings underscore that despite notable progress in Malaysia's flood risk management, significant deficiencies persist in policy execution, financial allocation, and public cognizance. This research refined the flood risk management conceptual framework to adapt to changing environmental contexts. Crucially, the proactive involvement of the federal government, local authorities from various Malaysian states, and the Department of Irrigation and Drainage Malaysia is indispensable in flood risk mitigation. While frameworks like the National Physical Plan 4 (NPP4) have improved, local planning must adapt them to local needs. Every development project should mandatorily embed a comprehensive flood risk assessment, ensuring alignment with national guidelines. This increases compliance and construction sector interest, elevating flood disaster risk reduction. This enables a future where innovation, professionalism, and knowledge improve life quality while prioritizing safety and sustainability.